BRICS Expansion and the Quest for a Multipolar World: Prospects and Challenges of Ethiopia’s Inclusion - (:unkn) unknown (My University, 2025)
The rise of BRICS forum as a platform that is attempting to change the international economic and political order marked a turning point in the history and development of contemporary international relations. Africa is mostly peripheral in the political and economic global decision making. This paper seeks to explore how Eastern Africa, with a focus on Ethiopia’s entry into BRICS as a full member of the forum, can navigate the evolving multipolar world order in the sense of prospects and challenges. Ethiopia is a potential powerhouse and a key player in the Eastern African sub region due to its massive population and economic opportunities. The paper adopts the neo-Gramscian theoretical framework, which is a critical theory that analyzed and interrogate the origin, nature and development of historical structures as well as it is a counter hegemonic theory. Findings of the paper shows that despite the fact Ethiopia’s inclusion as a full member of BRICS strengthened its bargaining power, being the least economy in the forum limits its influence. The study contributes to the discourse on South-South cooperation and Africa’s evolving role in global governance.
Keywords: African Research